A Fully Automated Method for Noisy cDNA Microarray Image Quantification - Fouad, Islam A.; Mabrouk, Mai S.; Sharawy, Amr A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–> DNA microarray is an innovative tool for gene studies in biomedical research, and its applications can vary from cancer diagnosis to human identification. Image processing is an important aspect of microarray experiments, the primary purpose of the image analysis step is to extract numerical foreground and background intensities for the red and green channels for each spot on the microarray. The background intensities are used to correct the foreground intensities for local variation on the array surface, resulting in corrected red and green intensities for each spot that can be considered as a primary data for subsequent analysis. Most techniques divide the overall microarray image processing into three steps: gridding, segmentation, and quantification. In this paper, aÂ Â simple automated gridding technique is developed with a great effect on noisy microarray images. A segmentation technique based on â€˜edge-detectionâ€™ is applied to identify the spots and separate the foreground from the background is known as microarray image segmentation. Finally, a quantification technique is used to calculate the gene expression level from the intensity values of the red and green components of the image. Results revealed that the developed methods can deal with various kinds of noisy microarray images, with high Â griddingaccuracy of 92.2% for low quality images and 100% for high quality images resulting in better spot quantification to getÂ more accurate gene expression values.Â <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>